Systemic Risk Index – Integrated Indicator of Financial Sustainability - Ivanets, Oleg (European Journal of Sustainable Development, 2017)
This paper contributes to the literature on financial sustainability in three major ways. First, it proposes a county-wide indicator of systemic risk that allows for including the risk factor into a broader macroeconomic analysis that was not done before. Second, it estimates systemic risk by financial assets, which is different from the common practice of estimating the risk by institutions. This approach allows for identifying risky assets that could lead to financial crises. By applying the model to the 1995-2016 data set, one can detect clear predictors of imminent crises. Finally, this paper estimates structural risk in the banking sector which is one of the major threats to the financial systems of developed countries. Keywords: systemic risk, financial sustainability, financial stability, financial crises